Nanocomposite electret with surface potential self-recovery from water dipping for environmentally stable energy harvesting - Li, Huayang; Guo, Zihao; Kuang, Shuangyang; Wang, Hailu; Wang, Ying; Wu, Tao; Wang, Zhong Lin; Zhu, Guang (Elsevier Ltd, 2019)
Due to their high charge densities, electret materials have gained extensive attention in recent years for their abilities to harvest mechanical energy. However, the environmental stability of electret materials is still a major concern for real applications. Here, we report a thin-film nanocomposite electret material (NCEM) that exhibits immediate and effective self-recovery of the surface potential after water dipping. The NCEM is composed of a polytetrafluoroethylene (PTFE) film, a nanocomposite film with PTFE nanoparticles as the nanofiller and polydimethylsiloxane (PDMS) as the matrix. The surface potential of the NCEM resulting from corona charging could be stably maintained with very little decay of 2% after 25 days. More importantly, the surface potential exhibited quick self-recovery to 75% and 90% of its initial value after 10 min and 60 min, respectively, when the NCEM was removed from water. A 70% self-recovery was still observed even when the NCEM was dipped in water for 200 cycles. When used in electret nanogenerators (ENGs), the electric output recovered to 90% even when the ENG experienced water dipping. Therefore, this work presents a key step towards developing high-performance and environmentally stable energy harvesting nanogenerators that can survive harsh conditions for real applications.